The Eros Thanatos Dilemma In Shewn’s Sun/Shine (2015): A Psychoanalytic Study - Hafiz Seno Pamungkas; Dwi Nur Cahyani Sri Kusumaningtyas (Samudra Ilmu Indonesia, 2026)
Song lyrics have become an important medium for representing psychological experiences and emotional struggles. Previous psychoanalytic studies have mainly examined defense mechanisms, inner conflict, and psychological aspects in various songs, while the psychological conflict between Eros and Thanatos in Shewn's Sun/Shine remains unexplored. Therefore, this study aims to analyze the representation of Eros, Thanatos, and the psychological conflict between these opposing instincts in the song. This research employs a qualitative approach using Freud's psychoanalytic theory. The data consist of the lyrics of Sun/Shine, which were analyzed through qualitative textual analysis. The findings reveal that Thanatos is represented through drowning, darkness, emotional suffocation, and identity loss, whereas Eros is represented through hope, sunlight, empathy, prayer, and the desire for recovery. The lyrics also portray psychological conflict through four binary oppositions: survival versus withdrawal, hope versus despair, connection versus isolation, and recovery versus emotional collapse. This study contributes theoretically to psychoanalytic literary criticism by extending Freud's theory to contemporary Indonesian independent music and practically by providing insight into how song lyrics represent psychological struggles through symbolic language.